Which is Worse, Unemployment or Inflation: The Comparison of the Effect of Unemployment and Inflation on Happiness - Morteza Khorsandi; Nastaran Alibabaie (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2016)
Since the unemployment and inflation are two target variables of economic policies and in many cases policy-makers have to sacrifice one for another, the question arises that what is the preferences of society between these two targets. The appropriate answer can be obtained when the effect of each variable on welfare is estimated and compared with each other. Therefore, in this paper, the effect of unemployment and inflation on happiness as an index of welfare is estimated. This estimation is done with two panel data samples. The first sample consist of 146 countries that happiness index is calculated for them and the second sample only includes Iran and its neighbors. The results show that in both cases unemployment has more effect on reducing happiness. In the sample of Iran and its neighboring countries, the absolute value of unemployment coefficient is 2.4 times higher than that of inflation. Accordingly, it can be concluded that in construction of social loss functions and also misery indices the weight of unemployment must be greater than inflation and the proposed relative weight for Iran is 2.4.